IMPROVING STUDENTS’ SPEAKING SKILLS THROUGH NARRATIVE VIDEOS FOR THE TENTH-GRADE SCIENCE STUDENTS AT SMAN 1 JAYAPURA - Elsa Afnidha (Journal of Education Papua Baru, 2022)
Abstract: The objectives of the study are: (1) To investigate whether the narrative video can improve the students of X-IA 5 in SMAN Jayapura speaking skills; (2) To measure the effectiveness of the narrative video in improving speaking skills (3) To know the situations of teaching and learning process in using narrative video as the teaching media. The research method used is pre-experimental research. The population of this study is the tenth-grade science students of SMAN 1 Jayapura in the academic year 2021/2022, and the sample is X-IA 5 class. The instrument used was test and observation. The result shows that there is a significant change proven by T-Test.  The pre-test mean was 23.53846154 and the post-test was 37.94871795. It brings a difference by 61.22%. The situation in the teaching-learning process using narrative video was interesting for almost all students in the classroom. It attracted them to learn to speak with friends and build self-confidence in front of the class. Based on the research above, the researcher concludes that narrative videos can improve students’ speaking skills effectively.Keywords: Improve, Speaking, Narrative, Video.